Facilitators, barriers and considerations for the implementation of healthcare innovation: A qualitative rapid systematic review. (23rd September 2021) - Parmar, Jasneet; Sacrey, Lori Ann; Anderson, Sharon; Charles, Lesley; Dobbs, Bonnie; McGhan, Gwen; Shapkin, Kimberley; Tian, Peter; Triscott, Jean
Abstract: Family caregiving scholars recommend that health providers receive competency‐based education to partner with and support family caregivers to care and to maintain their own health. While it may be relatively easy to develop competency‐based education for healthcare providers, ensuring widespread uptake and spread and scale of healthcare education is critical to ensuring consistent person‐centered support for all family caregivers (FCGs) throughout the care trajectory. The development of novel healthcare innovations requires implementation strategies for uptake and spread, with implementation involving the use of strategies to integrate a novel innovation into healthcare. Research suggests that there are many factors involved in successful implementation and a synthesis of potential factors is warranted. The purpose of this review is to provide an in‐depth examination of facilitators, barriers and considerations for implementation of a novel healthcare innovation that will be used to develop an implementation plan for spread and scale of our competency‐based education for health providers to learn about person‐centered care for FCGs. A systematic review of published and grey literature was conducted following the Preferred Reporting Items for Systematic Reviews and Meta‐analyses (PRISMA [Moher et al.,  2015]) guidelines. The systematic review involved searching four databases for original research articles that described barriers, facilitators and/or other considerations when implementing innovations. Twenty‐eight articles were included in the qualitative thematic analyses and described three areas of implementation research: barriers, facilitators and recommendations. There were major and parallel themes that emerged under facilitators and barriers. There were a wide variety of strategies that were identified as recommendations. The findings were synthesised into five considerations for implementation: Research and information sharing, intentional implementation planning, organisational underpinnings, creating the clinical context and facilitative training. This review provides an integrative overview of identified facilitators, barriers and recommendations for implementation that may aid in developing implementation strategies that can be tailored to the local context or innovation being implemented.